Kompleksowa diagnostyka wczesnych zmian w plamce w przebiegu zwyrodnienia plamki związanego z wiekiem - Kwiecień, Sława; Szaflik, Jacek P.; Szaflik, Jerzy (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
We demonstrated diagnostic cases of the early macular changes due to AMD, which caused central visual field disturbances. The aim of the study was to systemize the management in patients with macular lesions due to the age related macular degeneration, frequency determination and statement of the performed additional tests range. Patients reported central visual field distortions. We performed visual acuity testing, stereoscopic eye fundus examination, and PHP (macular visual field testing), which objectified distortions symptoms. Based on that tests and fellow eye condition, decision about OCT and FA and ICG performance were made. Further management was determined according to the results of that examinations: follow-up with vitamins and microelements supplementation or PDT. Our analysis confirm, that to monitor early macular changes due to AMD, follow-up examinations in 2-3 months interval are indicated: visual acuity testing, stereoscopic eye fundus examination and macular lesions modeling in PHP. In difficult cases or in more advanced lesions FA, OCT and ICG were performed.